1998
DOI: 10.1038/sj.ijo.0800624
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of intra-abdominal and subcutaneous abdominal adipose tissue in healthy pre-pubertal children

Abstract: OBJECTIVE: To examine the relationship of intra-abdominal adipose tissue (IAAT) and subcutaneous abdominal adipose tissue (SAAT) with body composition and anthropometry in children. DESIGN: Cross-sectional data analysis. SUBJECTS: 113 healty Caucasian and African-American, pre-pubertal children aged 4 ± 10 y. MEASUREMENTS: IAAT and SAAT by single slice computed tomography at the level of the umbilicus; total fat and trunk fat by dual energy X-ray absorptiometry (DEXA); anthropometric evaluation by skinfolds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
119
1
13

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(146 citation statements)
references
References 14 publications
12
119
1
13
Order By: Relevance
“…In this study, adiposity measurements were strongly correlated with each other, and adolescents with higher BMI also presented higher WC, TKFM, TFM and BF% values, indicating that in the population analyzed, BMI properly identified adiposity. Studies evaluating the distribution of fat in adolescents, with similar results of this study, found a strong association between BMI and WC (r = 0.88-0.91) (17,18) and between TFM and BMI (r = 0.84-0.97) (19,20). Especially in girls, BMI has been a good indicator of adiposity, because in females a greater fat deposition occurs during the pubertal period (21).…”
Section: Association Between Adiposity Indicators Metabolic Parametesupporting
confidence: 84%
“…In this study, adiposity measurements were strongly correlated with each other, and adolescents with higher BMI also presented higher WC, TKFM, TFM and BF% values, indicating that in the population analyzed, BMI properly identified adiposity. Studies evaluating the distribution of fat in adolescents, with similar results of this study, found a strong association between BMI and WC (r = 0.88-0.91) (17,18) and between TFM and BMI (r = 0.84-0.97) (19,20). Especially in girls, BMI has been a good indicator of adiposity, because in females a greater fat deposition occurs during the pubertal period (21).…”
Section: Association Between Adiposity Indicators Metabolic Parametesupporting
confidence: 84%
“…[1][2][3][4] Clustering of these CV risk factors in children and adolescents tends to track into adult life. [5][6][7][8][9] CV disease appears to be related specifically to intraabdominal fat (visceral adipose tissue) 10,11 of which waist circumference (WC) provides a good and clinically useful measure, [12][13][14][15][16][17] supporting the growing view that WC is a better measure of CV risk than body mass index (BMI) in both children and adults. [18][19][20][21] Ethnic differences of WC have been described in adults 22,23 but have not been studied in children, although reference data for WC are available from a number of different countries.…”
Section: Introductionmentioning
confidence: 97%
“…However, waist circumference is highly correlated with such techniques in children. 62 and has been widely used as the primary measure of central adiposity in many diet and exercise intervention studies. 10,45 Although we saw significant improvements with waist circumference alone, use of other methods may have improved the ability to see subtle changes, as well as localizing them to the subcutaneous or more metabolically important visceral space.…”
Section: Discussionmentioning
confidence: 99%